ChemInform Abstract: Synthesis, Structure and Reactivity of Rare‐Earth Metal Complexes Containing Anionic Phosphorus Ligands. Issue 14 (8th April 2014) - Li, Tianshu; Kaercher, Sabrina; Roesky, Peter W.
Abstract Review: 49 refs.